Uncomplicated midvaginal vesico-vaginal fistula repair in Ibadan: a comparison of the abdominal and vaginal routes (2008)
Background: Obstetric fistula is a resultant effect of prolonged obstructed labour. The best surgical management of simple uncomplicated fistula determines the outcome of care. Objective: To compare outcome of uncomplicated mid-vaginal fistula between vaginal and abdominal route of repair. Materials and Method: This was a hospital based retrospective study conducted at the University College Hospital, Ibadan from January, 2000 till December, 2006. Result: Of the 71 midvaginal fistulae managed, 40.8% had abdominal repair while the remainder were through vaginal approach. The overall repair success rate was 79.2% with comparable outcome in both groups-78.3% for the abdominal and 80% for the vaginal group (p=0.999). The duration of hospital stay did not differ significantly between the groups (p=0.972). Post operative complications were found in 41.4% of the abdominal group compared to none in the vaginal group (p<0.001). The complications were failed repair (20.7%) and urinary tract infection (20.7%). The mean estimated blood loss was 465.5ml in the abdominal group compared to 332.9ml for the vaginal group (p=0.303). Conclusion: Despite the comparable surgical repair outcome of the two methods, the vaginal approach is associated with lesser blood loss and lower risk of post-operative complications. It is recommended that the vaginal route should be employed in the repair of uncomplicated midvaginal fistula unless there are other compelling reasons to the contrary